UI/UX Design of Waste Management Application Using Design Thinking Method - Regar Chairul Soleh; M Maukar (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Effective and sustainable waste management is a global challenge that requires innovative solutions. This study proposes optimizing waste management through UI/UX design approach using the design thinking method. The stages of Empathize, Define, Ideate, Prototype, and Testing are employed to design the "SISAKU" mobile application to enhance community participation in waste management. The prototype testing involved 30 respondents, with a System Usability Scale (SUS) result of 80.29%. Evaluation shows that the application design successfully provides intuitive and engaging guidance, increasing public awareness and involvement in waste management. The implementation of lean canvas as a business model provides strategic direction for sustainable development. This research highlights the importance of a user-centered design approach and design thinking method in addressing complex issues such as waste management.